LOAD BALANCING ALGORITHM FOR GRID TASK SCHEDULING IMPROVEMENT - Svirin, Pavlo V. (Information and Telecommunication Sciences, 2014)
In order to satisfy the users' requirements for the productivity and efficiency of tasks implementation the grid-system should implement the effective algorithm of tasks distribution between the computing resources accessible at the moment. The primary purpose of such load balancing in the grid-system is to reduce the time necessary for the user's task implementation. Moreover, it will provide efficient usage of the computing resources and eliminate such a situation that some resources stand idle when the other are overloaded with users' tasks implementation.